Systemic Banking Crises : A New Database - Valencia, Fabian (IMF Working Papers; Working Paper ;, 2008)
This paper presents a new database on the timing of systemic banking crises and policy responses to resolve them. The database covers the universe of systemic banking crises for the period 1970-2007, with detailed data on crisis containment and resolution policies for 42 crisis episodes, and also includes data on the timing of currency crises and sovereign debt crises. The database extends and builds on the Caprio, Klingebiel, Laeven, and Noguera (2005) banking crisis database, and is the most complete and detailed database on banking crises to date.